Scalar vs. vector approach to bi-objective resource allocation in spatially distributed networks. (1st January 2013) - Filipič, Bogdan; Vesanen, Risto; Laitinen, Erkki
The problem of optimal resource allocation in spatially distributed networks appears, for example, in wireless telecommunications and consists of maximising the network utility, i.e., the fee paid by the users, and minimising the costs of installing the allocated resources. This bi-objective optimisation problem can be approached in several ways, and we investigate the potentials of two fundamentally different ones: a scalar approach that starts with transforming the problem into a single-objective form and then solves it using an appropriate optimisation method, and a vector approach based on evolutionary computation. We provide the problem formulation, present the two approaches and report on numerical experiments and results obtained on test problem instances.